Peningkatan Kemampuan Siswa Menghitung Volume Balok dan Kubus Melalui Pem-anfaatan Media Bangun Ruang - Saidah, Ida; Aca, Aca (Jurnal Tata Kelola Pendidikan, 2024)
This research aims to improve students' skills in calculating the volume of cubes and blocks through the use of spatial construction media at Blungbang elementary school. The research method used is classroom action research with a quantitative approach. The research subjects were 30 grade 6 students at Blungbang elementary school. Collecting primary and secondary data using observation, testing, and documentation methods. Observations were carried out to observe students' ability to calculate the volume of cubes and blocks, while tests were used to measure students' reading abilities, and documentation was used to see students' activity during reading lessons. Data analysis was carried out using qualitative and quantitative approaches. The results of the research show that the level of students' ability to calculate the volume of cubes and blocks for class 6 Blungbang elementary school before the classroom action research was carried out was still low. However, after two learning cycles using spatial media, there was a significant improvement. In the first cycle, there was an increase of 44.44% with an average value of 62.44%, and in the second cycle, it reached 100% with an average value of 78.55. The use of spatial construction media in class 6 has proven to be very influential in improving students' ability to determine the volume of cubes and blocks. So it can be concluded that the application of geometric learning media in teaching the concept of volume of cubes and blocks in grade 6 can produce a significant increase in student learning outcomes.